(untitled) (Emancipação, 2024)
The designation of quilombola territories has recently emerged as a prominent issue in Brazil, prompting scrutiny from diverse analytical perspectives. In light of this context, this paper endeavors to interrogate the acknowledgment of territorial rights within the remaining quilombo communities through the framework of Critical Theory, particularly leveraging the insights of Axel Honneth (2003). To achieve this objective, supplementary data were procured from governmental bodies overseeing policy enactment, along with various electronic media sources. The investigation was informed by empirical evidence garnered from qualitative research centered on quilombola communities, conducted in Rio Grande do Sul in 2018. This research, instrumental in shaping a doctoral thesis, furnished updated information for this paper. Despite formal acknowledgment, it is evident that quilombola communities persist in their struggle for the realization of their rights, an endeavor that endures alongside the implementation of public policy.